MENJELAJAHI HUBUNGAN LEVEL ARGUMENTASI DENGAN KEMAMPUAN BERFIKIR KRITIS SISWA DALAM MENYELESAIKAN SOAL IKATAN KIMIA - Haruna, Asriani; Nahadi, Nahadi (Universitas Negeri Semarang, 2021)
Critical-thinking skill refers to the main ability to help individuals to prevent mistaken in choosing any decision to overcome problems. One proven learning mode to be able to develop and improve students' critical thinking skills is by implementing an argumentation strategy with the ADI (Argumentation-Driven-Inquiry). This study describes the relationship between the level of argumentation and students' critical thinking skills on chemical bonding material. The research is focused on 1) identification of studentsÃ¢â‚¬â„¢ argumentation 'level and 2) identification of students' critical thinking skills after applying the ADI model. The participants were the tenth-year high school students of one of the schools in South Sulawesi, Indonesia. The sample was selected with cluster random sampling technique. The instrument consists of multiple-choice questions and essay to identify students' critical thinking skills and rubrics to determine the level of student argumentation. The result shows that the studentsÃ¢â‚¬â„¢ ability to make arguments have a strong connection to their ability to answer the given critical-thinking-skill test. However, several weaknesses found at criteria K4 (K4 criteria), that is the ability to analyze problems.Ã‚Â